The Pavlo Tychyna’s Neology Through the Prism of Folk Tradition (Linguostylistic Studies, 2015)
In the registry forming process of author’s lexical new-formations of P. Tychyna it was found out that folklore juxtapositions are fixed by mistake, so the register forming of the folkloryzms-juxtaposition’s dictionary is actual. The attempt of formation of the registry of «Dictionary of the composite folkloryzms» on more than 3,000 units was realized. The source base of it are 112 collections of folklore. The purpose of the article is to determine the influence of folklore texts on the author’s lexical new-formations of Pavlo Tychyna. The tasks of the paper are: the analysis of extralinguistic factors that contributed P. Tychyna’s borrowing of the examples of folk art; to clarify the causes of folkloryzms’ using in the process of word creation’s experiments. Determination of folk origin of author’s new-formations is a complex process that involves monitoring of the folklore texts, researching of the bio-bibliographic data about the life and career of the poet, analysis of special folkloristic, ethnographic, ethno-linguistic literature and making repeated examination of the register of author’s new-formations of Pavlo Tychyna. One of the key features of this study is the national cultural specificity, which also provides the key to understanding of the nature of the origin of innovation. Key words: аuthor’s lexical new-formation, Pavlo Tychyna, word creation, Ukrainian poetry of XX century, folklore, folkloryzm. References